Comparative Effectiveness of Drug-Coated Balloon vs Balloon Angioplasty for the Treatment of Arteriovenous Fistula Stenosis: A Meta-analysis. (April 2020) - Cao, Zhanjiang; Li, Jiazheng; Zhang, Tong; Zhao, Keqiang; Zhao, Junlai; Yang, Yu; Jiang, Chao; Zhu, Rongrong; Li, Zipeng; Wu, Weiwei
Purpose: To compare the effectiveness and safety outcomes of drug-coated balloon angioplasty (DCBA) vs conventional balloon angioplasty (BA) for arteriovenous fistula (AVF) stenosis.Materials and Methods: A systematic review was conducted of PubMed and Embase databases from 1966 to May 2019 to identify English-language articles evaluating DCBA vs BA for the treatment of AVF stenosis. Data extracted from each study were synthesized to evaluate target lesion revascularization (TLR), technical success, and mortality for the 2 approaches. Meta-analyses were performed on these outcomes using random effects models to estimate the odds ratios (ORs) and 95% confidence intervals (CIs). Subgroup and sensitivity analyses were performed.Results: Twelve studies [6 randomized controlled trials (RCTs) and 6 cohort studies] comprising 979 patients were included in this meta-analysis. The pooled results showed that AVFs treated with DCBA had significantly fewer TLRs at 6 months (OR 0.31, 95% CI 0.14 to 0.69, p=0.004) and 12 months (OR 0.45, 95% CI 0.21 to 0.97, p=0.04) than BA. The 2 approaches had similar technical success rates (OR 0.22, 95% CI 0.03 to 1.43, p=0.11). Additionally, the pooled OR of 12-month mortality was 0.71 (95% CI 0.20 to 2.51, p=0.60), indicating no significant difference between DCBA and BA. Subgroup analysis based on study design showed the superiority of DCBA to BA in cohort studies but not RCTs, which had high heterogeneity. Significant publication bias was found in the cohort studies.Conclusion: In de novo or recurrent AVF stenosis, DCBA appears to be an effective procedure associated with lower 6- and 12-month TLR compared with BA. However, larger and randomized controlled studies are warranted to draw definitive conclusions.